ANALYSIS OF BUSINESS DEVELOPMENT STRATEGY FOR SCHOOL EDUCATIONAL TOOLS THROUGH THE BUSINESS MODEL CANVAS APPROACH (Case Study of PT. Prima Duta Nusantara) - Kholid Harisudin; Donny Setiawan (Prodi Manajemen Bisnis Syariah, 2025)
Constraints have been identified in the business strategy of PT. Prima Duta Nusantara, a manufacturing company that lacks a specific strategy for its operations. This has hindered optimal growth, particularly in a competitive manufacturing industry. The research aims to analyze and formulate development strategies for the company using the Business Model Canvas (BMC) approach. A descriptive qualitative method was employed, with data collected through interviews, observations, and documentation. Results show that while PT. Prima Duta Nusantara has started using the BMC, it has not fully addressed all elements or created written mappings. Based on the current BMC, a new and improved version has been designed to guide future business development.